(3GdUMGaI GdGdcJQhfjI (B:s (3OQGSI aj JaGYd bQGA GdUMa GdGdcJQhfjI GdLRGFQjI (B/s - (3HhadGbI, cQjeIs ((3GdLRGFQ (B:s (3cQjSJGd ,s, 2010)
(3MbbJ GdUMGaI GdGdcJQhfjI GdeSJajOI ef JWhQ THcI GdGfJQfjJ aj fMh YbO h fUa ef GdReGf eGYLRJ Yf JMbjbg GdUMGaI GdeWHhYI aj YTQGJ GdSfjf h CMOKJ JZjQGJ edMhXI aj echfGJ GdYedjI GdGJUGdjI GdJbdjOjI GdJj cGfJ JbJUQ Ydi GdeQSd h GdeSJbHd h GdQSGdI h GdhSjdI h CYdJ ef TGf HYV GdechfGJ GdJj cGfJ gGeTjI aj GdGJUGd GdJbdjOj h aJMJ GdWQjb CeGe GdfGS ddJeJY HeRjO ef MQjI GdJYHjQ (B. s
Keywords: (3GdGdcJQhfjI s; (3GdUMGaIs